RELATIONSHIP OF OBESITY AND STRESS WITH HYPERTENSION EVENTS IN WOMEN IN NADGALO PADANG HEALTH CENTER - fitria alisa; Anes Yerden Trivina (Jurnal Vokasi Keperawatan (JVK), 2020)
Hypertension is a condition where an increase in blood pressure above normal. High prevalence of hypertension occurs in women. in Sumbar hypertension in women reaches 24%, and in Puskesmas Nanggalo reaches 7.53%. Factors of hypertension in women are obesity and stress. The purpose of this study was to determine the factors associated with the incidence of hypertension in women at the Nanggalo Padang Health Center. This research uses descriptive analytic cross sectional design. Data collection was conducted at Nanggalo Public Health Center in Padang with a sample of 57 people, with accidental sampling technique. Retrieval of data using primary data collected through questionnaires and weighing BMI and secondary data obtained from the documentation study at Padang Nanggalo Public Health Center. Data were processed with SPSS using univariate analysis of frequency distribution and bivariate chi- square test.The results of the study are known from 57 respondents 66.7% who suffer from hypertension, 78.4% respondents who are obese, 80% respondents are stressed Bivariate analysis showed that there was a relationship between. The relationship between obesity and hypertension (p= 0.024 ? 0.05). The relationship between stress and hypertension (p=0.030 ? 0.05). From the results of this study the incidence of hypertension in women is related to the use obesity and stress. Suggestions for health workers to further improve counseling about healthy eating and exercise to prevent hypertension.